Customized healing abutments: case report. - Assada, Fábio (2019)
When installing an immediate implant, you can choose between installing a temporary clinical crown, healing abutments, or to close the implant for a two-step surgical treatment. The use of customized healing abutments seals the implants and leads to individualized healing, which favors the creation of subsequent crowns. The present study aims to report a clinical case involving an immediate implant and the installation of customized healing abutments, demonstrating the results and the importance of knowledge of this technique by the dentist.